Non-state Actors and International Criminal Law - Novokmet, Rutvica Rusan (The ICC at 25: Lessons Learnt, 2025)
The legal position of non-state actors in international law has been on the agenda of international scholars for several decades, particularly in terms of defining various kinds of non-state actors, clarifying the issue of their international legal personality, and, ultimately, addressing the most controversial question – that of their international responsibility. In this context, the author analyses the position of armed opposition groups as a specific category of non-state actors in situations of non-international armed conflicts, in which violations of international law frequently occur. The author thus defines the international legal framework relevant for the regulation of the rights and duties of these non-state actors, and places special emphasis on violations of international legal norms amounting to the most serious international crimes. The author warns that there is a legal lacuna in respect of the international responsibility of armed opposition groups since the international criminal law framework still does not offer adequate legal and institutional mechanisms for holding them directly accountable as groups.However, the reality of international relations and the enormous extent and gravity of international crimes committed by armed opposition groups in armed conflicts advocate for recognition of their direct international responsibility. Such a view is supported by an increasing number of scholars, the jurisprudence of international courts and tribunals, and Security Council decisions, all of which are analysed in this paper. The author concludes that, in order to complement the international criminal justice framework, all the aforementioned actors should enhance their cooperation and find more suitable solutions for explaining the role of armed opposition groups as collectives in the commissioning of international crimes, as well as for defining the prerequisites for their direct international responsibility. The author also offers possible solutions in this regard.Keywords: non-state actors, armed opposition groups, international humanitarian law, international human rights law, international crimes, direct international criminal responsibility